Agents and Artificial Intelligence 7th International Conference, ICAART 2015, Lisbon, Portugal, January 10-12, 2015, Revised Selected Papers - Duval, Béatrice.; Duval, Béatrice.; van den Herik, Jaap.; van den Herik, Jaap.; Loiseau, Stephane.; Loiseau, Stephane.; Filipe, Joaquim.; Filipe, Joaquim. (Lecture Notes in Artificial Intelligence, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Conference on Agents and Artificial Intelligence, ICAART 2015, held in Lisbon, Portugal, in January 2015. The 18 revised full papers presented in this book were carefully reviewed and selected from 187 submissions. The papers are organized in two topical sections on agents and on artificial intelligence and focus on multi-agent systems and software platforms; distributed problem solving and distributed AI in general; knowledge representation; planning; learning; scheduling; perception; reactive AI systems; and evolutionary computing.